Urolithin A Alleviates Osteonecrosis and Is Associated With Regulation of SIRT3 in Osteoclasts - Yi Xue; Donghua Fan; Pu Ying; Tong Lu; Yufan Ge; Jingliang Zhang; Xiaomeng Xue (Discovery Medicine, 2026)
Background: Urolithin A (UA) is a safe and promising therapeutic strategy for aging-related disorders, including osteoporosis. Sirtuin 3 (SIRT3) has been reported as a potential modulator of bone-joint pathologies such as osteoclast activation. However, whether UA affects osteoclast activation and function through SIRT3 remains unclear. This study aims to elucidate the mechanisms by which UA alleviates osteonecrosis.Methods: Primary bone-marrow-derived macrophages (BMMs) were isolated from mice, treated with Macrophage Colony-Stimulating Factor (M-CSF) and Receptor Activator of Nuclear Factor-κB Ligand (RANKL). Mature osteoclasts were identified by Tartrate-Resistant Acid Phosphatase (TRAP) staining to assess differentiation. Cell viability was measured with Cell Counting Kit-8 (CCK-8) assays. The expression of osteoclast-related protein was detected by Western blot, and its mRNA level was detected by quantitative Real-Time polymerase chain reaction (qRT-PCR). The effects of UA on osteoclast mitophagy and mitochondrial respiration were assessed using Western blot and a Seahorse analyzer. Osteonecrosis of the femoral head was evaluated by hematoxylin and eosin staining (H&E), Safranin O/Fast Green, and TRAP staining. SIRT3 protein levels were assessed by Western blot.Results: In vitro, UA (3 μM) significantly decreased the number of TRAP-positive osteoclasts (p < 0.05) and downregulated the expression of osteoclast-related genes (Acid phosphatase 5 (Acp5), cathepsin K (Ctsk), Matrix metallopeptidase 9 (Mmp9), Integrin subunit beta 3 (Itgb3), ATPase H+ transporting V0 subunit d2 (Atp6v0d2); p < 0.05). UA treatment reduced SIRT3 protein levels (p < 0.05), elevated ATPase inhibitory factor 1 (ATPIF1) acetylation, and suppressed receptor-mediated mitophagy markers (BCL2/adenovirus E1B interacting protein 3-like (Nix) and BCL2/adenovirus E1B 19 kDa protein-interacting protein 3 (Bnip3); p < 0.05) in osteoclasts, while impairing mitochondrial respiration and increasing mitochondrial ROS production. SIRT3 overexpression partially reversed these effects. In vivo, UA administration attenuated cartilage thinning, trabecular collapse, and reduced TRAP-positive cells and SIRT3/Nuclear factor of activated T cells, cytoplasmic 1 (NFATc1) expression (p < 0.05) in a glucocorticoid-induced osteonecrosis mouse model.Conclusion: UA effectively inhibits osteoclast activation and alleviates glucocorticoid-induced osteonecrosis, and its protective effects are associated with downregulation of SIRT3 expression as well as the expression of mitophagy-related markers Nix and Bnip3. UA may represent a potential therapeutic candidate for osteoclast-mediated bone disorders.